Konflik Peran Ganda dan Beban Kerja: Pengaruhnya terhadap Kinerja Perawat Wanita Menikah di RSUD - Chandra, Felix (Management Studies and Business journal, 2025)
The  primary objective of this study was to examine the partial influence of dual role conflict and workload on the performance of married female nurses at Saparua Regional Hospital. The background of this research lies in the fact that female nurses often encounter challenges in balancing professional responsibilities with family roles, which can potentially diminish their performance quality. This study employed a quantitative approach using a survey method. The respondents consisted of 33 married female nurses who were actively working at Saparua Regional Hospital. The sample was selected through a purposive sampling technique based on specific criteria. Data were collected using a five point Likert-scale questionnaire designed according to the indicators of each variable. Before proceeding with the analysis, validity and reliability tests, as well as classical assumption tests, were conducted to ensure that both the instruments and the analytical model were appropriate. Subsequently, multiple linear regression analysis was applied to evaluate the contribution of each independent variable to performance. The findings revealed that both dual role conflict and workload had a significant negative effect on nurse performance. This indicates that the greater the role conflict or workload experienced, the lower the performance level achieved by married female nurses.